AESTHETICS AND POLITICAL PERSUASION IN CONTEMPORARY SAUDI ARABIAN POETRY ON NEOM: A SOCIOLOGICAL ANALYSIS OF LITERATURE - Muhammad Firmansyah; Ade Kosasih; Ooh Hodijah; Abdul Barr Nashir (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2026)
Literature has become an important tool for expressing and validating ideas about the future of the country as Saudi Arabia increases its cultural and symbolic commitment in the Neom megaproject. This article analyzes how award-winning poems from a Neom-themed poetry competition held by Nadi Tabuk Adabi function both as aesthetic representations of the Neom project and as instruments of ideological conditioning in contemporary Saudi Arabia. Employing a qualitative descriptive method, this study draws on Alan Swingewood’s sociology of literature to examine poetry as a social product shaped by institutional and political contexts. Hermeneutic textual analysis is applied to three winning poems, focusing on diction, metaphor, symbolism, and narrative structure, while situating these elements within their socio-political environment. The findings show that Neom is consistently represented as a utopian, transformative, and inevitable future through futuristic imagery. Beyond textual representation, the poetry competition itself operates as a cultural institution that conditions meaning production through prestige, recognition, and symbolic legitimacy rather than coercion.This research contributes to Arabic literary studies by demonstrating the continued political function of poetry in contemporary state-sponsored cultural practices and by framing modern Arabic poetry as a site of ideological negotiation rather than purely aesthetic expression.